MAY-THURNER SYNDROME: THE IMPORTANCE OF IVUS IN THE DIAGNOSTIC AND THERAPEUTIC ALGORITHM - Machado, Marta (2021)
Introduction : May Thurner Syndrome (MTS) is a clinical condition as a result of an anatomical compression of the left common iliac vein by the fifth lumbar vertebra posteriorly, and by the right common iliac artery anteriorly associated with symptomatology. Affirming the diagnosis can be difficult and intravascular ultrasonography (IVUS) can help in the definitive decision. Clinical Case: A 43 years old man with a past history of a deep venous thrombosis of the left lower limb presented at our clinical appointment with a 5 months history of left limb edema and inability to stand up for long periods of time, disabling him from working.A venous-CT scan was obtained to diagnose the condition but was inconclusive. It was proposed to the patient to carry out a phlebography and an IVUS to eliminate the doubt and increase the diagnosis acuity, which was accepted.A phlebography and IVUS confirmed a significant compression of the left common iliac vein (image 1).The patient was treated by endovenous placement of an Abre 16/80 medtronic stent followed by dilatation with a 16/40 balloon Boston scientific. The phlebography and IVUS control showed complete resolution of the compression. (Image 2) Discussion/Conclusion: The diagnosis of MTS can be difficult and implies a high degree of clinical suspicion.The TC scan alone may not be diagnostic. The phlebography, and especially the more recent IVUS technology increases the accuracy of the diagnosis.Emergence of endovascular surgery revolutionized the treatment of obstructive venous disease, and became the gold standard of treatment. However, the implantation of stents in a young population implies additional cautions due to the lack of knowledge about their behavior over the long term.In this clinical case, the IVUS allowed us to reach the diagnosis and to increase the therapeutic accuracy of the ilio- cava stenting. We recommend the routine use of IVUS in the management of MTS.